Unusual dynamic polarization response and scaling behaviors in Bi1/2Na1/2TiO3 ceramics. (January 2019) - Wang, Jun; Zhou, Changrong; Li, Qingning; Zeng, Weidong; Xu, Jiwen; Chen, Guohua; Yuan, Changlai; Rao, Guanghui
Graphical abstract: (a) Electric field amplitude ( E 0 ) dependence of P - E hysteresis loops measured at 0.1 Hz. The inset (b) shows hysteresis area < A > of the hysteresis loops with variation E 0 . (c), (d) are the plots of ln P r, ln E c, ln< A > and dln< A >/dln E 0 versus ln E 0 . Here, the polarization reversal and dynamic hysteresis were investigated in (Bi1/2 Na1/2 )TiO3 (BNT) ceramics. The scaling behaviors were presented by studying the dependence of hysteresis loops on the field amplitude E 0 . New feature of polarization responses and scaling behaviors were obtained. The exponent α in an equation of the hysteresis loop area < A >∝ E 0 α displayed large values in high- E 0 stage. Highlights: The exponent α in the hysteresis loop area < A >∝ E 0 α equation shown large values in high- E 0 stage. The < A > displayed abnormal increase with temperature. A near frequency-invariant coercive field E C, accompanied by a weakly dependent P r and < A > was observed. Abstract: The excellent electrical properties and potential applications of ferroelectric ceramics are intrinsically correlated with the dynamic polarization response under applied electric field. However, the lack of clarity with regard to global polarization reversal process has hindered the understanding of the functional properties. Here, the polarization reversal and dynamic hysteresis were investigated in (Bi1/2 Na1/2 )TiO3 (BNT) ceramics. The scaling behaviors were presented by studying the field amplitude E 0, frequency f 0 and temperature T 0 dependence of hysteresis loops. Three new features of polarization responses and scaling behaviors were obtained. First, the exponent α in the hysteresis loop area < A >∝ E 0 α equation displayed large values in high- E 0 stage. Then, the < A > displayed an abnormal increase with increasing temperature. Finally, a near frequency-invariant coercive field E C, accompanied by a weak dependent P r and < A >, was observed. The correlation between these new features and polarization extension/rotation as well as complex domain structure and field-induced phase transition was demonstrated.